Best 11 selection using machine learning - Anik, Aminul Islam; Yeaser, Sakif; Hossain, A.G.M. Imam (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.